EVALUATION OF KNOWLEDGE, SELF-PERCEIVED CONFIDENCE AND MANAGEMENT OF PERIODONTAL PATIENTS AMONG GENERAL DENTISTS - Sadia Musharraf; Waleed Ahmed Ismail; Nasar Um Min Allah; Sohaib Arshad; Zain Iftikhar; Waleed Mushtaq (Pakistan Oral & Dental Journal, 2022)
The incidence of tooth loss due to advanced periodontal diseases are on the rise because of the unawareness of basic periodontal treatment needs by the majority of general dentists (GDs) in Pakistan. This cross-sectional study was carried out to evaluate the periodontal knowledge, treatment strategies being used, referral profile and level of confidence of GDs regarding their provision of periodontal care. A pre-validated, self-administered, structured questionnaire-based survey was used, comprising of 16 questions, with a combination of open and closed-ended questions. A total of 300 participants were reached for the data collection. The data were collected and analysed by using SPSS version 26. The response rate was 36.6% (n=110). The results showed that the majority 84 (76%) of the GDs were running their practices for less than 5 years with most of them were males 58 (53%). The majority 88 (80%) of the study participants referred their patients to specialist periodontists. The major (46%) cause of referral was a lack of response to initial periodontal therapy performed by themselves (50%) after basic periodontal examination at their practices. Ninety-nine (90%) participants stated that a visiting periodontist was needed for a private clinical setup. This study concluded that there was an increasing trend of referring patients to periodontists by the GDs. The current knowledge of awareness about diagnosis, treatment strategies, and referral profile of GDs were adequate however, a very low inclination 36 (33%) towards continuing dental education programs on periodontal therapy was expressed which should be addressed.
Keywords: Awareness; General dentists; Periodontal disease; Oral hygiene; Treatment strategies